Students’ Perceptions of Preparation for Online Graduate Course Work - Carver, Lin B; Rivera-Singletary, Georgina (Advances in Social Sciences Research Journal, 2020)
An anonymous online survey was used to understand participants’ perceptions about their preparation for online coursework. Sixty students from five graduate programs in education completed a 1-4 Likert scale survey with 20-questions and six open-ended responses. Quantitative responses from the 20 questions were divided into two subgroups, those younger than or equal to 40 years of age, and those over 40 years of age based on Prensky’s date for the beginning of the digital native group. Qualitative data were collected through 6 open-ended questions from the same survey. Data revealed that both subgroups felt well prepared when registering for online courses. However, when it came to overall preparedness for using technology, those over 40 years of age did not view themselves as well prepared as those younger than 40. Using digital resources outside of the learning management system presented more significant challenges to the older subgroup of learners. Two factors impacting graduate students’ online performance became evident through this study; the impact of technology experience rather than age and what is meant for a student to be well-prepared for online course work.